Avancées récentes sur la reproduction des huîtres - Gerard, Andre (La pisciculture française, 1998)
Historically, the research on mollusc reproduction conducted by the Ifremer aimed at improving mass production in order to support new activities (Japanese clam for example) or to compensate for insufficient natural reproductions (abalone, king scallop). Nowadays, priority has been given to the preservation of natural resources and the optimisation of shellfish culture in order to support activities that are strongly represented by a profession, especially oyster culture. The studies that have been carried out in the field of oyster genetics for about ten years highlighted the limits of our knowledge on reproduction control as well as the high sensitivity of mollusc farms to the multiple assaults of their outside environment. As far as professional hatcheries' needs are concerned, mass egg-layings by genitors are usually sufficient to ensure spat production. In order to resolve some constraints linked to the development of genetic selection programs, namely the protection of the strains from outside aggressions and the testing of the performances in strictly identical environmental conditions, some oyster production trials in a totally controlled environment (underwater treated saltwater) have been carried out. The first results are good and enable us to foresee their partial application in professional hatcheries, at least for the larval stage. Historiquement les recherches sur la reproduction des mollusques à l'IFREMER étaient destinées à l'amélioration des productions en masse en vue de soutenir des activités nouvelles (palourde japonaise par exemple) ou pour pallier à des reproductions naturelles insuffisantes (Ormeau, Coquille St Jacques). De nos jours, la priorité est donnée à la préservation des ressources naturelles et il l'optimisation de la conchyliculture en soutien aux activités fortement représentées par une profession, en particulier l'ostréiculture. Les recherches engagées dans le domaine de la génétique des huîtres depuis une dizaine d'année ont fait ressortir les limites de nos connaissances ...